"Inverted" Deep Eutectic Solvents Based on Host‐Guest Interactions. Issue 23 (28th November 2019) - Yu, Dongkun; Mou, Hongyu; Fu, Hui; Lan, Xue; Wang, Yingxiong; Mu, Tiancheng
Abstract: Herein, the concept of "inverted" (the mode "molecules mainly interact with cations") deep eutectic solvents (DESs) is proposed. A strategy to form inverted DESs by host‐guest interactions was developed, and thus numerous DESs could be designed and formed by a combination of host and guest molecules. These liquids are expected to be used as nonaqueous electrolytes in potassium‐ion batteries or other fields for further exploration. Abstract : The concept of inverted deep eutectic solvents (DESs) is proposed. In "conventional" DES, the anion of the ionic compound interacts with the molecular compound, while in the "inverted" DES, the cation of the ionic compound interacts with the molecular compound.